Differentially Expressed Gene Pathways in the Conjunctiva of Sjögren Syndrome Keratoconjunctivitis Sicca - de Paiva, Cintia S.; Trujillo-Vargas, Claudia M.; Schaefer, Laura; Yu, Zhiyuan; Britton, Robert A.; Pflugfelder, Stephen C. (Frontiers in Immunology, 2021)
Sjögren syndrome (SS) is an autoimmune condition that targets the salivary and lacrimal glands, with cardinal clinical signs of dry eye (keratoconjunctivitis sicca, KCS) and dry mouth. The SS conjunctiva is often infiltrated by immune cells that participate in the induction and maintenance of local inflammation. The purpose of this study was to investigate immune-related molecular pathways activated in the conjunctiva SS patients. Female SS patients (n=7) and controls (n=19) completed a series of oral, ocular surface exams. Symptom severity scores were evaluated using validated questionnaires (OSDI and SANDE). All patients fulfilled the ACR/EULAR criteria for SS and the criteria for KCS. Fluorescein and lissamine green dye staining evaluated tear-break-up time (TBUT), corneal and conjunctival disease, respectively. Impression cytology of the temporal bulbar conjunctiva was performed to collect cells that were lysed and subjected to gene expression analysis using the NanoString Immunology Panel. 53/594 differentially expressed genes (DEGs) were observed between SS and healthy controls; 49 DEGs were upregulated and 4 were downregulated (TRAF5, TGFBI, KLRAP1, and CMKLRI). The top 20 DEGs in descending order were BST2, IFITM1, LAMP3, CXCL1, IL19, CFB, LY96, MX1, IL4R, CDKN1A, SERPING1, HLA-DRB3, S100A8, IRF7, ICAM1, C4A/B, TNFAIP3, CD74, HLA-B, and TAP1. 20 pathways had a global significance score greater or equal to 2. Spearman correlations showed that 29/49 upregulated DEGs correlated with either TBUT (inverse) or OSDI or conjunctival staining score (positive correlations). Venn diagrams identified that 26/29 DEGs showed a correlation with TBUT; 5/26 DEGs correlated with OSDI and 16/26 correlated with conjunctival staining score. Five upregulated DEGs (CFB, CFI, IL1R1, IL2RG, IL4R) were uniquely negatively correlated with TBUT. These data indicate that the conjunctiva of SS patients exhibits a phenotype of immune activation, although some genes could be inhibitory. Some of the DEGs and pathways overlap with previous DEGs in salivary gland biopsies, but new DEGs were identified, and some of these had a correlation with symptoms and signs of dry eye. Our results indicate that gene analysis of conjunctiva imprints is a powerful tool to understand the pathogenesis of SS and develop new therapeutic targets.